Pengaruh Corporate Governance terhadap Pengungkapan Corporate Social Responsibility (CSR) pada Perusahaan Sektor Pertambangan yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2022 - Ilahi, Vivi Anugrah; Cheisviyanny, Charoline (Jurnal Nuansa Karya Akuntansi, 2024)
This research will to examine the influence of corporate governance on CSR disclosure. The scope of the research includes mining sector companies with a sample of 19 companies selected using the purposive sampling method. This research was conducted by analyzing 57 companies listed on the Indonesia Stock Exchange during the 2020-2022 period. The secondary data analysis technique used is multiple regression analysis using SPSS software. The research results show that the size of the board of commissioners and the frequency of audit committee meetings have a positive and significant effect on CSR disclosure. Meanwhile, the independent board of commissioners, frequency of board of commissioners meetings, size of the audit committee, managerial ownership, institutional ownership, foreign ownership and partial public ownership have no effect on CSR disclosure.